Kinerja Implementasi Program Pendaftaran Tanah Sistematis Lengkap di Desa Soddara Kecamatan Pasongsongan Kabupaten Sumenep - Dinda Alfania Kharisma; M. Hadi Makmur; Tree Setiawan Pamungkas (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2023)
This study aims to describe the implementation’s performance of Complete Systematic Land Registration (PTSL) program in Soddara Village Pasongsongan Subdistrict Sumenep Regency. The basis for this research is the problem of the land area owned by the community, which is not yet legally documented and raises land disputes. The Village Government is trying to solve the problem by proposing the implementation of the Comprehensive Systematic Land Registration (PTSL) program to the Sumenep Regency Land Office. The approach and research method used is qualitative with the type of data consisting of primary data and secondary data obtained through interview, observation, and documentation techniques. The validity of data was tested using the data triangulation technique. Analysis of the data using the interactive model of Miles, Huberman, and Saldana. The result showed that out of eight implementation’s performance described by Ripley, only accountability aspects were not found in this study. Keywords: Implementation; PTSL